Analisis Kalibrasi Bangunan Ukur Debit Cipoletti - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK One of the problems in the management of irrigation system is water irrigation distribution accuracy, which k actually measured by discharge measurement structure. The government usually underestimates discharge measuremem structure, especially its maintenance and rehabilitation. This condition will cause inaccurate discharge measurement. It h very important to study the preservation of the structure function accuracy. Structure function preservation is required through periodical calibration. Current meter is inadequate or even no